2013
DOI: 10.1007/s11274-013-1264-x
|View full text |Cite
|
Sign up to set email alerts
|

From crude glycerol to carotenoids by using a Rhodotorula glutinis mutant

Abstract: In this work eighteen red yeasts were screened for carotenoids production on glycerol containing medium. Strain C2.5t1 of Rhodotorula glutinis, that showed the highest productivity, was UV mutagenized. Mutant 400A15, that exhibited a 280 % increase in β-carotene production in respect to the parental strain, was selected. A central composite design was applied to 400A15 to optimize carotenoids and biomass productions. Regression analyses of the quadratic polynomial equations obtained (R(2) = 0.87 and 0.94, for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
49
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(56 citation statements)
references
References 28 publications
1
49
0
5
Order By: Relevance
“…Mantzouridou et al [14] found that a maximum productivity of carotenes (9.4 and 29.4 mg/g dry biomass/day) was obtained when B. trispora was grown in crude olive pomace oil and crude soybean oil, respectively. The maximum carotene productivity was 0.03-2.9 mg/g dry biomass/day (0.2-16.5 mg/l/day) when several agro-industrial by-products such as whole stillage, corn steep liquor, parboiled rice water, hydrolyzed mung bean waste flour, grape must, fermented radish brine, crude glycerol, wheat straw, grape juice, and molasses were used as substrates for carotene production by Phaffia rhodozyma, Sporobolomyces roseus, Sporidiobolus pararoseus, Cystofilobasidium capitatum, R. glutinis, R. mucilaginosa, recombinant industrial wine yeast, and Arthrobacter globiformis in shake flask culture and stirred tank fermentor [1,5,[15][16][17][18][19][20][33][34][35]. The cited results show that the amounts of carotenes produced from different agro-industrial by-products were very low compared with our results, that is, 55.5 mg/g dry biomass/day (405.0 mg/l/day) using bubble column reactor and deproteinized hydrolyzed whey supplemented with Tween 80, Span 80, and β-ionone.…”
Section: Effect Of the Aeration Rate On Carotene Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mantzouridou et al [14] found that a maximum productivity of carotenes (9.4 and 29.4 mg/g dry biomass/day) was obtained when B. trispora was grown in crude olive pomace oil and crude soybean oil, respectively. The maximum carotene productivity was 0.03-2.9 mg/g dry biomass/day (0.2-16.5 mg/l/day) when several agro-industrial by-products such as whole stillage, corn steep liquor, parboiled rice water, hydrolyzed mung bean waste flour, grape must, fermented radish brine, crude glycerol, wheat straw, grape juice, and molasses were used as substrates for carotene production by Phaffia rhodozyma, Sporobolomyces roseus, Sporidiobolus pararoseus, Cystofilobasidium capitatum, R. glutinis, R. mucilaginosa, recombinant industrial wine yeast, and Arthrobacter globiformis in shake flask culture and stirred tank fermentor [1,5,[15][16][17][18][19][20][33][34][35]. The cited results show that the amounts of carotenes produced from different agro-industrial by-products were very low compared with our results, that is, 55.5 mg/g dry biomass/day (405.0 mg/l/day) using bubble column reactor and deproteinized hydrolyzed whey supplemented with Tween 80, Span 80, and β-ionone.…”
Section: Effect Of the Aeration Rate On Carotene Productionmentioning
confidence: 99%
“…However, utilization of a synthetic medium is not economical and the exploitation of a less expensive medium could prove beneficial. Numerous agro-industrial by-products such as crude olive pomace oil, crude soybean oil, whole stillage, grape juice, grude glycerol, wheat straw, parboiled rice water, corn steep liquor, and molasses have been considered as potential carbon sources for biotechnological production of carotenes by different strains of fungi, yeasts, and bacteria [5,[14][15][16][17][18][19].…”
mentioning
confidence: 99%
“…Furthermore, they are intensively applied for food and beverage coloration (Downham and Collins, 2000; Gassel et al, 2013). Hence, carotenoids have received extensive considerable attention and especially the interest for an efficient and environmental-friendly production by microbial hosts is increasing (Lee and Schmidt-Dannert, 2002; Das et al, 2007; Harada and Misawa, 2009; Cutzu et al, 2013). In order to compete with already existing production processes, such as chemical synthesis or extraction from organic material, the large-scale production in microbial hosts requires process as well as strain optimization.…”
Section: Introductionmentioning
confidence: 99%
“…About 10% (w/w) crude glycerol is the main byproduct produced in the biodiesel manufacture process [7]. Since the global production of biodiesel is increasing, the amount of crude glycerol production has also greatly increased, and consequently its market price has reduced leading to crude glycerol being a very promising potential substrate for the cultivation of oleaginous microorganisms [3,8,9]. In addition to the substrate's falling cost, the operating cost for the accumulation of microbial oils is also a major concern for the commercial viability of microbial oils.…”
Section: Introductionmentioning
confidence: 99%